Antiracist Academic Leadership in Wake of Charlottesville - David S Owen (Academic Chairpersons Conference Proceedings, 2019)
What obligations do chairpersons have to confront white supremacy when it impacts departmental and campus climates? And, what steps should chairpersons take when white nationalists come to campus? Participants in this session will have an opportunity to discuss these and other questions and explore the requirements of academic leadership that is avowedly antiracist.
Keywords: Anti-racism; leadership; ethics; white nationalism; white supremacy; campus climate; inclusion; equity